The effect of supportive counseling on stress reduction in women undergoing colposcopy: a quasi-experimental study - Fatemeh Hemmati; Roghaiyeh Nourizadeh; Nooshin Mobaraki; Khalil Esmaeilpour; Esmat Mehrabi (Payesh, 2023)
Objective(s): In the case of abnormal Pap smear, colposcopy is recommended. Women referred for colposcopy experience high levels of stress. The present study aimed to evaluate the effect of supportive counseling on stress reduction in women undergoing colposcopy. Methods: This quasi-experimental study was performed on 72 women undergoing colposcopy in Ardabil, Iran. Participants were randomly assigned into two groups. The intervention group received supportive counseling during three sessions ‎every three days. The control group only received a pamphlet containing information on colposcopy. The data were collected using perceived stress scale. Independent t-test, and ANCOVA were used to analyze the data. Results: There was no significant difference in demographic and obstetrics characteristics of the participants (P> 0.05). Before counseling, the mean score (SD) of stress in the intervention group was 35 (4.24) and it was 33.54 (5.13) in the control group (P= 0.217). After counseling, the mean score of stress was not significantly different between the two groups [AMD: 0.93, 95% CI: -1.40 to 3.27, p =0.428]. Conclusion: Supportive counseling could not reduce the stress. Using other stress management strategies such as cognitive restructuring and mindfulness in women undergoing colposcopy might worth for suggeting the future studies.